214 No socioeconomic differences in overall survival seen in patients with advanced ovarian cancer where parity of access to treatment and cytoreductive outcomes can be achieved. (13th November 2020) - Watson, L; Hatfield, T; Lavender, G; Phillips, A
Abstract : Introduction: The impact on socioeconomic status on survival in advanced ovarian cancer (AOC) is controversial. Whilst previous epidemiological studies suggested no socioeconomic differences in survival in AOC, more recent studies found that less deprived patients may have longer overall survival (OS) due to a greater utilisation of treatment and better outcomes from those treatments. The aim of this study was to investigate whether any socioeconomic differences were evident in patients treated at a cancer centre serving a well-defined population and what impact, if any, the implementation of a change in surgical paradigm had on this disparity. Methods: A retrospective review of 679 patients with Advanced Stage 3 and 4 Epithelial Ovarian, Tubal and Fallopian tube cancer (AOC) diagnosed between 6th January 2003 and 29th March 2019. All patients were classified by UK postcode using the Index Multiple Deprivation (IMD) into five groups. Data was collected on OS, treatment approach and cytoreductive outcomes. Results: No difference was seen in access to surgery or cytoreductive outcomes obtained by IMD group. Across the entire cohort no significant difference in OS was seen across the five groups. When comparing the patients before and after a change towards extensive surgery in 2014, again, no significant difference in OS was seen. Conclusions: Assuming parity of exposure to treatment and outcomes can be achieved, we witnessed no disparity in AOC survival by socioeconomic group. Improving access to and quality of care in all patients is likely to reduce any socioeconomic differences in survival.